Mobilidade urbana e entregas do e-commerce: análise das relações entre frete cobrado do cliente final, prazos, características dos produtos e dos locais de entrega - Rafael Fernandes Ferreira (2019)
The increase of the population who live in urban areas is a proven worldwide fact. However, a proper planning cover does not monitor the urbanization reinforcement. Such fact lead to ways that do not comprise a great flow of vehicles, which takes to degradation of urban mobility. The low mobility affects the low shipping of the companies, which raises its cost and reduces the service level. For e-commerce companies, the delivery of the goods is one of the main elements that influence client satisfaction, therefore reducing mobility can influence the profitability. This paper aims to understand the effects of urban mobility in shipping delivery services of e-commerce companies. In order to do that, purchases from different products were simulated in e-commerce companies, which deliver their goods in different levels of urban mobility regions. The collected freights were analyzed through descriptive statistics, correlation analyzes, average trial and classification and regression tree. To complement the results it was applied a semistructured interview with reps from different organizations related to the delivery of goods, the purpose of such interview is to understand the pricing process and the effects of urban mobility at this operation from a practical perspective. The result from analyzing the data points that, there is no statistical difference of shipping for deliveries in regions with both high and low mobility levels. Such fact can be explained due to the lack of strategic allocation to logistics, by the companies, and also for the high volume of deliveries in low mobility regions, which makes the high cost of them be shared because by its high number.